Development of LGAD sensors with a thin entrance window for soft X-ray detection. (1st November 2022) - Zhang, J.; Barten, R.; Baruffaldi, F.; Bergamaschi, A.; Borghi, G.; Boscardin, M.; Brückner, M.; Carulla, M.; Centis Vignali, M.; Dinapoli, R.; Ebner, S.; Ficorella, F.; et al.
Abstract: We show the developments carried out to improve the silicon sensor technology for the detection of soft X-rays with hybrid X-ray detectors. An optimization of the entrance window technology is required to improve the quantum efficiency. The LGAD technology can be used to amplify the signal generated by the X-rays and to increase the signal-to-noise ratio, making single photon resolution in the soft X-ray energy range possible. In this paper, we report first results obtained from an LGAD sensor production with an optimized thin entrance window. Single photon detection of soft X-rays down to 452 eV has been demonstrated from measurements, with a signal-to-noise ratio better than 20.